ANALISIS PENGUJIAN TAN DELTA PADA TRANSFORMATOR ARUS DI GITET TASIKMALAYA BAY PENGHANTAR BANDUNG SELATAN-1 - Harris Rifqi Febrijanto; Rahmat Hidayat (TEKNOKOM, 2023)
Current transformers are essential for substation protection. It converts large currents into smaller currents that are used for measurement and triggering protection systems. Errors in the conversion of electric current can lead to measurement inaccuracies and protection system failures. Improper maintenance and use can shorten the life of the transformer and also lead to earlier system failure. One of the tests applied is the tan delta test to determine the loss coefficient of the insulating material. A decrease in insulation quality increases the tan delta value. The capacitance value is also measured in the tan delta test. An increased capacitance value indicates the paper insulation has been damaged. Generally, damaged insulation causes a short circuit between capacitor layers which is characterized by an increase in capacitance value. By using the GST-Ground method with the Megger Delta 4110 measuring instrument, the tan delta results of the R, S, and T phases in the southern send bay of Bandung-1 GITET Tasikmalaya are 0.42%, 0.47%, and 0.45%. The results of independent calculations are phase R, S, T are 0.29%, 0.28% and 0.31%. From both results, the current transformer can be said to be feasible to operate because the tan delta value is below 1% which is the operational standard of the current transformer.